Farming, slaving and enslavement: histories of endosymbioses during kinetoplastid evolution - Harmer, Jane; Yurchenko, Vyacheslav; Nenarokova, Anna; Lukeš, Julius; Ginger, Michael L (Parasitology, 2018)
Parasitic trypanosomatids diverged from free-living kinetoplastid ancestors several hundred million years ago. These parasites are relatively well known, due in part to several unusual cell biological and molecular traits and in part to the significance of a few - pathogenic Leishmania and Trypanosoma species - as aetiological agents of serious neglected tropical diseases. However, the majority of trypanosomatid biodiversity is represented by osmotrophic monoxenous parasites of insects. In two lineages, novymonads and strigomonads, osmotrophic lifestyles are supported by cytoplasmic endosymbionts, providing hosts with macromolecular precursors and vitamins. Here we discuss the two independent origins of endosymbiosis within trypanosomatids and subsequently different evolutionary trajectories that see entrainment vs tolerance of symbiont cell divisions cycles within those of the host. With the potential to inform on the transition to obligate parasitism in the trypanosomatids, interest in the biology and ecology of free-living, phagotrophic kinetoplastids is beginning to enjoy a renaissance. Thus, we take the opportunity to additionally consider the wider relevance of endosymbiosis during kinetoplastid evolution, including the indulged lifestyle and reductive evolution of basal kinetoplastid Perkinsela.
Keywords: molekulární evoluce; genom protozoální; Symbiosis; Novymonas esmeraldas; biologická evoluce; biodiverzita; Genome, Protozoan; Biological Evolution; Pandoraea; Kentomonas; cytostome; Kinetoplastida; Angomonas deanei; symbióza; Leishmania; Trypanosomatina; Biodiversity; Candidatus Kinetoplastibacterium; Trypanosoma; Evolution, Molecular